The “dot-in-circle” sign in musculoskeletal mycetoma on magnetic resonance imaging and ultrasonography - Laohawiriyakamol, Teeranan (Springerplus, 2014)
This study aimed to present the ‘dot-in-circle’ sign, which indicates the typical magnetic resonance imaging (MRI) and ultrasonographic (USG) findings for mycetoma involving soft tissue and bone. A total of 8 cases with histopathological proof of mycetoma affecting the musculoskeletal system, and that were examined via MRI and/or coexistent diagnostic ultrasonography between 2004 and 2013 in Songklanagarind Hospital were included in this study. The ‘dot-in-circle’ sign on the MRI and USG images of all the patients was reviewed by two radiologists. The analytic method was descriptive. All cases of musculoskeletal mycetoma revealed the ‘dot-in-circle’ sign on MRI, which was seen as multiple, small, round- to oval-shaped hyperintense lesions separated and surrounded by a low-signal intensity rim (circle), and a tiny, central, low-signal focus (dot). An USG study was available in four patients, and all USG findings demonstrated the ‘dot-in-circle’ sign as a central hyperechoic area (dot) surrounded by hypoechoic tissue (circle). In conclusion, the ‘dot-in-circle’ sign is a typical feature on MRI and USG findings for the diagnosis of musculoskeletal mycetoma.